PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN BANTUAN MODUL TERHADAP HASIL BELAJAR SISWA PADA MATERI LAJU REAKSI - Ayu Pepri Ramadeni; Elvi Yenti (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
It was a quasi-experimental research with pretest and posttest design, and it was conducted to two classes—experimental and control groups. This research was instigated by the low of student chemistry learning achievement at the eleventh grade of Natural Science of State Senior High School 5 Pekanbaru. This research aimed at knowing the effect of implementing Guided Inquiry learning model with module toward student learning achievement on Reaction Rate lesson at the eleventh grade of Natural Science of State Senior High School 5 Pekanbaru. The samples were two the eleventh-grade classes of Natural Science having the same homogeneity level. The eleventh-grade students of Natural Science 5 were the experimental group and the students of Natural Science 2 were the control group. Simple random sampling technique was used in this research. The techniques of collecting the data were interview, preliminary data test that was homogeneity test, final data tests that were pretest and posttest, and documentation. The analysis results showed that the posttest mean score of the experimental group was 85.63 and the control group was 78.75. Final data analysis that t-test was used showed that the score of t​observed 3.08 was higher than t​table 2.00 at 5% significant level, so H​0 was rejected and H​a was accepted. It meant that there was an effect of implementing Guided Inquiry learning model with module toward student learning achievement on Reaction Rate lesson at the eleventh grade of Natural Science of State Senior High School 5 Pekanbaru, and the coefficient of effect was 14%